ANALISIS KESULITAN YANG DIHADAPI GURU DALAM KURIKULUM MERDEKA DI KELAS 2 DAN 4 DI SD NURUL QOMAR - Amri Amri; Aulia Mardiana; Cinta Ramadhani; Pebrijah Nasution; Siti Azzuhra Fadhillah (Kampus Akademik Publiser, 2024)
Education is a very important factor for the development of a country. Education helps develop and improve skills and improve the quality of life and human dignity. Until now, changes have been made to the curriculum. The curriculum is considered a plan developed to facilitate the teaching and learning process which is the responsibility of the school or educational institution and its teaching staff. (Yulia, 2023). This study examines various difficulties faced by teachers in implementing the Merdeka Curriculum in elementary schools. The Free Curriculum, designed to provide more flexibility and creativity in the learning process, requires significant adjustments from teachers. Some of the key challenges identified include a lack of in-depth understanding of the concept and implementation of the new curriculum, limited resources and support facilities, and resistance to changes from some teachers who are familiar with conventional methods. In addition, the high administrative burden and time constraints for professional development also complicate the situation. This study used qualitative methods with in-depth interviews of a number of elementary school teachers in various regions to collect data. Research results show that continuous support, intensive training, and adequate provision of resources are indispensable to overcome these obstacles and ensure effective and efficient implementation of the Free Curriculum.